Common Phenotype in Patients with Both Food and Substance Dependence: Case Reports - Campbell, HB (2013)
The understanding that genes play a significant role in reward dependence and associated behavioral and drug addictions is highlighted in the emergence of Reward Deficiency Syndrome (RDS). Here we show two case reports that unequivocally indicate the definite commonality between food and drug addiction. These human cases not atypically raise the question as to how to treat these two seemingly diverse addictions. We suggest that research directed in an attempt to induce natural activation of dopaminergic reward circuitry as a form of common therapy may indeed be parsimonious.